2021
DOI: 10.5465/amj.2018.0620
|View full text |Cite
|
Sign up to set email alerts
|

Gaining Legitimacy by Being Different: Optimal Distinctiveness in Crowdfunding Platforms

Abstract: We are very grateful to Zeki Simsek and three anonymous reviewers for their support and many insightful suggestions that have substantively improved our article throughout the review process. We also thank Jeff Covin, Mark Healey, Joseph Lampel, and Silvia Massini for their insights and helpful comments on earlier drafts of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
180
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(187 citation statements)
references
References 76 publications
(151 reference statements)
4
180
1
2
Order By: Relevance
“…His multi‐industry study showed that the distinctiveness–performance relationship can systematically differ between categories, where the performance benefits of a distinctive positioning are greatest in categories in which competitors occupy relatively similar positions. Taeuscher et al (2020) outlined that evaluating audiences differ in their tolerance of nonconformity and appreciation of novelty and distinctiveness, and highlighted that such audience‐level characteristics can shape both benefits and liabilities of distinctiveness. Studying optimal distinctiveness in the context of crowdfunding, they find that the benefits of distinctiveness can strictly exceed the opposing liabilities in contexts in which audiences demonstrate a high tolerance of nonconformity and actively seek out novel and distinctive offerings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…His multi‐industry study showed that the distinctiveness–performance relationship can systematically differ between categories, where the performance benefits of a distinctive positioning are greatest in categories in which competitors occupy relatively similar positions. Taeuscher et al (2020) outlined that evaluating audiences differ in their tolerance of nonconformity and appreciation of novelty and distinctiveness, and highlighted that such audience‐level characteristics can shape both benefits and liabilities of distinctiveness. Studying optimal distinctiveness in the context of crowdfunding, they find that the benefits of distinctiveness can strictly exceed the opposing liabilities in contexts in which audiences demonstrate a high tolerance of nonconformity and actively seek out novel and distinctive offerings.…”
Section: Discussionmentioning
confidence: 99%
“…These findings strongly suggest that access to even one alternative source of legitimacy-high-status complementors-can provide a buffer against an immediate loss in legitimacy, and such legitimacy buffers increase-to a certain degree-the optimal level and performance benefits of distinctiveness. These findings have important implications for research on optimal distinctiveness (Barlow et al, 2019;Haans, 2019;Taeuscher, Bouncken, & Pesch, 2020;Zhao et al, 2018) because they draw attention to intra-market heterogeneity in firms' optimal distinctiveness-highlighting firms' legitimacy buffers as an important contingency for the theorized trade-off between differentiation and conformity.…”
Section: Introductionmentioning
confidence: 87%
“…Entrepreneurship is in need of gaining legitimacy for attracting of resources and clients, which is complicated because of their liability of newness (Täuscher et al 2020). For the question of entrepreneurs can achieve legitimacy we have to consider the fundamentals of institutional theory which broadly defines an institution a set of rules that govern behavior of actors (Selznick 1996).…”
Section: Fundamentals Of Institutional Theorymentioning
confidence: 99%
“…External relationships cross organizational boundaries (Bouncken and Fredrich 2016b;Pesch and Bouncken 2017). They can improve legitimization and attractiveness and bring resources (Täuscher et al 2020). Especially the young organizations of coworking spaces and their individual or entrepreneurial actor require legitimacy for their actions, specifically from other actors that provide physical, human, financial, or reputational resources (Dacin et al 2007;Dacin 1997;Suchman 1995).…”
Section: Layers and Loops Out Of The Flexible Border Among Internal Amentioning
confidence: 99%
“…The keyword "legitimacy" also shows that the institutional entrepreneur cannot act unboundedly but depends on external approval (Garud et al 2002). However, legitimacy does not necessarily relate to established institutions but can also be based on distinctness (Taeuscher et al 2020).…”
Section: Keyword Co-occurrence Analysismentioning
confidence: 99%